Experimental study on die shoulder patterning method (DSPM) to reduce springback of U-bending hat-shape part (in Press) - Nurul Jannah, Baharuddin; Ahmad Rosli, Abdul Manaf; Ahmad Shahir, Jamaludin (Center for Research Innovation Management, UTeM, 2021)
In the sheet metal industry, such as car door pillars, U-bending is becoming more common. However, when extracting sheet metal from fixtures, the springback phenomenon often occurs, resulting in a change in product efficacy, waste of material, and an increase in production costs. As a result, minimising springback in sheet metal bending is critical for maintaining tight geometric tolerances in the deformed component. Experiments and simulations have been used by several researchers to investigate and predict the occurrence of springback. Regardless, no studies on the application of die shoulder patterning to reduce springback in hat-shaped parts have been conducted. The hat-shaped component is deformed in this paper using a new develop forming process, which has been tested and validated using new finite element prediction. As predicted, die shoulder patterning dominates springback sensitivity, with hat-shaped parts having a lower springback due to a larger contact region. Springback is greatly reduced in AISI 1030 due to the optimised sliding tension between the die shoulder and the blank board.